Examining The Impact of Hustle Culture on South Korean Workers - Hasanah, Ummul; Vardhani, Nabilla Kusuma; Martha, Fajarasih Luthfia (Universitas Gadjah Mada, 2024)
In recent years, the term hustle culture has often been heard among young workers. Through a hustle culture, a company's progress, which ultimately affects a country's progress, will be possibly achieved more quickly. However, criticism has been common that hustle culture interferes with the mental health of workers in a company because they are too overworking. South Korea has long been known as a country with workers carrying out a hustle culture. This culture can be seen in some of the depictions of Korean popular culture, such as in the Korean drama